Environmental pollution liability insurance pilot policy and enterprise green transformation: evidence from Chinese listed corporates - Hu, Ling; Liu, Ziming; Liu, Pengzhen (Frontiers in Ecology and Evolution, 2023)
In the context of dual-carbon, corporate green transformation, a significant measure of the green effect of Environmental Pollution Liability Insurance (EPLI), garners substantial attention in current research. By leveraging the 2008 EPLI pilot policy as an exogenous event, this paper employs a difference-in-difference model to scrutinize the influence of the EPLI pilot on the green transformation of listed companies. We find that: (1) The EPLI pilot actively promotes corporate green transformation. (2) The pilot policy's impact on green transformation is mediated through regional green development and enterprise investment efficiency. (3) The pilot policy manifests asymmetric effects on green transformation, influenced by regional, industrial, and enterprisespecific pollution levels, as well as government environmental concerns. (4) The EPLI pilot policy engenders enduring financial implications and contributes to the governance of information. This study is beneficial to enrich the research on the EPLI system and green transformation of enterprises that provide policy suggestions for improving the green financial system and promoting the green transformation of enterprises.